2019
DOI: 10.1002/hed.25746
|View full text |Cite
|
Sign up to set email alerts
|

CASP9 c.‐1339A>G and CASP3 c.‐1191A>G polymorphisms alter susceptibility and clinical aspects of head and neck squamous cell carcinoma

Abstract: Background Single nucleotide polymorphisms (SNPs) in genes that act in intrinsic apoptosis pathway may modulate cancer susceptibility. This study investigated the roles of CASP9 c.‐1339A>G (rs4645978) and CASP3 c.‐1191A>G (rs12108497) SNPs on risk and behavior of head and neck (HN) squamous cell carcinoma (SCC). Methods DNA of 350 patients with HNSCC and 350 controls was analyzed by polymerase chain reaction method for genotyping. Results CASP3 c.‐1191AG or GG genotype was more common in patients with HNSCC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Secondly, it was found that the TT genotype of TNFRSF1B c.587T>G SNV was more common in younger patients (patients aged ≤54 years compared to older patients), a common aspect of tumors with unequivocal genetic components, such as those of hereditary syndromes [ 50 , 51 ] and familial tumors [ 52 , 53 ], which are, respectively, determined by high and low penetrance mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it was found that the TT genotype of TNFRSF1B c.587T>G SNV was more common in younger patients (patients aged ≤54 years compared to older patients), a common aspect of tumors with unequivocal genetic components, such as those of hereditary syndromes [ 50 , 51 ] and familial tumors [ 52 , 53 ], which are, respectively, determined by high and low penetrance mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental data here obtained were further confirmed by performing computational analyses of publicly available miRNA-gene interaction and miRNAs expression databases, including miRWalk, TCGA HNSC database and miRCancerdb. These bioinformatics analyses demonstrated the inhibitory action of hsa-miR-133a-3p and hsa-miR-375-3p towards a total of 147 genes of which some are involved in several molecular and biological processes underlying tumor development, including TP53, SHANK2, CASP9, etc., whose dysregulation is notoriously observed in oral cancer [45][46][47].…”
Section: Discussionmentioning
confidence: 99%